Effects of Lubricant Additives on Tribological Properties of Piston Ring-Cylinder Liner Friction Pair - AHEBOTA·Baheti, DU Xue-ling, E Hong-jun, JIN Jia-jia (Cailiao Baohu, 2023)
In order to study the influence of common additives in lubricating oil， such as friction improvers， antifriction agents and detergents，on the tribological properties of engine piston ring-cylinder liner friction pair， and to explore their interaction mechanism， the effects of SN/GF-5 0W-20 engine oil， molybdenum dialkyl dithiocarbamate (MoDTC)， zinc dialkyl dithiophosphate (ZDDP) and calcium sulfonate detergent on the piston ring-cylinder liner were studied using the piston ring-cylinder liner friction pair of SRV©4 multifunctional friction and wear tester.Furthermore， the friction film on the wear surface of the cylinder liner was analyzed by SEM and XPS. Results showed that the content of MoDTC in SN/GF-5 0W-20 engine oil would affect its tribological performance. When the content of Mo element was 0.50%(mass friction)，the tribological performance was the best. The ZDDP/MoDTC lubrication system had a good synergistic effect and could significantly reduce the friction coefficient. The introduction of calcium sulfonate detergent into the ZDDP/MoDTC lubrication system reduced the formation of MoS2 friction film and increased the friction coefficient.